PROPAGANDA IDEOLOGI BUSHIDO DALAM FILM DJAGALAH TANAH DJAWA PADA MASA PENDUDUKAN JEPANG - Adi Putra Surya Wardhana (Handep: Jurnal Sejarah dan Budaya, 2021)
This study aims to describe the propaganda of bushido ideology in the film Djagalah Tanah Djawa published during the Japanese occupation era. Japan had limited natural and human resources to face the Allies in the Pacific War. Java was seen as a region capable of meeting Japanese needs. Propaganda was needed so that the Japanese internalized the bushido ideology to the Javanese population. Some research problems are (1) the form of bushido ideology deeply held by the Japanese people; (2) the function of Japanese propaganda on Java; (3) the meaning of bushido ideology represented by the Propaganda Film Djagalah Tanah Djawa during the Japanese occupation. The research used the historical method. The research shows that bushido ideology influenced the whole outlook of life and social practices of Japanese society, especially during the Pacific War. This ideology was internalized in the propaganda film Djagalah Tanah Djawa. Its function was to attract Javanese people to be willing to take part in the Japanese program. The meaning stated that victory over the Allied occupation could only be achieved if the Javanese people made sacrifices and cooperated with Japan to realize “New Java”.’ Thus, Japan could dominate the consciousness and unconsciousness of the Javanese population.